Analisis Distribusi Khi Kuadrat dalam Penelitian Statistik - Ramadhan, Zidhan Moro; Kaharap , Benie Agusti; Parhusip, Jadiaman (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Chi-square distribution represents a fundamental statistical concept with strategic importance across interdisciplinary scientific research, offering a sophisticated analytical instrument for exploring hidden patterns in categorical data and hypothesis testing. This comprehensive study examines the mathematical characteristics, statistical properties, and practical applications of chi-square distribution, highlighting its unique capability to capture variations and uncertainties in data with high precision. By investigating its theoretical complexity and methodological versatility, the research demonstrates how chi-square distribution serves as an intellectual tool enabling researchers to systematically explore empirical realities across diverse fields such as psychology, sociology, medicine, and engineering, providing a robust framework for statistical inference and scientific knowledge generation.